Legal analysis of freedom of expression with special reference to broadcasting media in Pakistan - Fatiana, Yasir Aleem (2020)
Freedom of expression is one of the most cherished fundamental rights. Freedom of expression is imperative in all fields including media. Ever since the emergence of electronic media in Pakistan, the freedom of expression has also received more attention. Pakistan Electronic Media Regulatory Authority (PEMRA) was created in 2002 and subsequently governed by an ordinance, PEMRA Ordinance 2002, to regulate electronic media in Pakistan. Electronic media includes broadcast media and distribution services. The Constitution of Pakistan and different laws including PEMRA Ordinance 2002 and the Electronic Media (Programs and Advertisements) Code of Conduct 2015 afford various restrictions on freedom of expression of broadcast media. This study critically analyses as to how and to what extent freedom of expression of broadcast media is protected and restricted in Pakistan. For better insights on the subject, this study also comprehends the laws and practices of different countries such as Malaysia and United Kingdom, and considers international perspectives relating to freedom of expression of broadcast media. To achieve the objectives of the study, doctrinal legal research method was adopted. It was further supported by socio-legal research method. Under socio-legal research method, semistructured interviews were conducted. This study finds, among others, that there are numerous issues annexed with freedom of expression of broadcast media in Pakistan. These issues have seriously affected the applicability of the principle of freedom of expression and also restricted the prospects of effective regulation of broadcast media in Pakistan. Consequently, the study sets out some recommendations such as amending the laws related to freedom of expression of broadcast media, in particular, PEMRA Ordinance 2002. This study also articulates clearer guidelines on the Code of Conduct of the electronic media. It is expected that the proposed amendments will resolve the prevailing issues of freedom of expression of broadcast media and pave the way for the PEMRA to work as more autonomous and effective regulatory body for the electronic media in the country.